The Fundamental Concept of Crime in International Criminal Law A Comparative Law Analysis - Marchuk, Iryna; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book examines the rapid development of the fundamental concept of a crime in international criminal law from a comparative law perspective. In this context, particular thought has been given to the catalyzing impact of the criminal law theory that has developed in major world legal systems upon the crystallization of the substantive part of international criminal law. This study offers a critical overview of international and domestic jurisprudence with regard to the construal of the concept of a crime (actus reus, mens rea, defences, modes of liability) and exposes roots of confusion in international criminal law through a comprehensive comparative analysis of substantive criminal laws in selected legal jurisdictions.
Keywords: Law; Criminal Law; Law; International Criminal Law; Private International Law, International & Foreign Law, Comparative Law; Theories of Law, Philosophy of Law, Legal History; Public International Law; Criminal Law